The effect of blood pressure variability on the prognosis of patients with acute cerebral hemorrhage: Possible mechanism - Sun, Xiangrong; Jv, Xinyue; Mi, Qi; Yang, Qian; Chen, Tao; Jiang, Guohui (Frontiers in Neuroscience, 2022)
Background Antihypertensive therapy in the acute phase of intracerebral hemorrhage (ICH) can reduce hematoma expansion. Numerous studies have demonstrated that blood pressure variability secondary to antihypertensive therapy has adverse effects on neurological outcomes, but the conclusions are diverse, and the mechanism of this occurrence is unknown. The aim of this research was to analyze the impact of blood pressure variability after antihypertensive treatment on the prognosis of patients with acute ICH, along with the possible mechanism. Materials and methods A total of 120 patients within 20 h of onset of ICH were divided into a good prognosis group (mRS ≤ 2 points) and a poor prognosis group (mRS ≥ 3 points) according to their 90-day mRS scores. The basic patient information, NIHSS score, GCS score, mRS score at 90 days after admission, head CT examination at admission and 24 h and CTP examination at 24 h were collected from some patients. The blood pressure values of patients were collected within 24 h, and multiple blood pressure variation (BPV) parameters within 1 and 24 h were calculated. Results (1) After excluding confounding factors such as age, whether the hematoma ruptured into the ventricle, confounding signs, amount of bleeding, edema around the hematoma, NIHSS on admission, operation or non-operation, and 24-h hematoma increment, the fourth quartile systolic blood pressure (SBP) maximum and minimum difference within 1 h [OR: 5.069, CI (1.036–24.813) P = 0.045] and coefficient of continuous variation (SV) within 24 h [OR: 2.912 CI (1.818–71.728) P = 0.009] were still independent factors affecting the 90-day mRS in ICH patients. (2) There was a negative correlation between SBP SV and CBF in terms of the difference between the contralateral side and the perihematomal region at 24 h (Rs = −0.692, P = 0.013). Conclusion Blood pressure variability after antihypertensive therapy in acute ICH is one of the influencing factors for 90-day mRS in patients. A 1-h dramatic drop in SBP and 24-h SBP SV may affect the long-term prognosis of patients by reducing whole cerebral perfusion.